The influence of lifestyle on peak bone mass in Norwegian boys and girls between 15-19 years of age. The Tromsø study, Fit Futures - Nilsen, Ole Andreas (UiT The Arctic University of Norway, 2021)
Background: Osteoporotic fractures constitute a major health- and economic burden worldwide and because of an aging population the burden is estimated to rise. The individual consequences of fractures are severe. Norway has one of the highest fracture incidences in the world. The etiology of fracture risk at old age is less optimal bone mass accumulation in childhood and adolescence, rapid subsequent age-related bone loss or a combination of both. Therefore, peak bone mass (PBM) is a predictor of future fracture risk and to optimize bone accretion in young age, identification of predictors of modifiable factors are critical. Objectives: The aim of this thesis was to describe changes in bone traits during two years in late adolescence, investigate the degree of tracking of those bone traits and explore the associations between lifestyle factors such as body weight and snuff use and bone mineral density changes in Norwegian girls and boys between 15-19 years of age. Methods: In 2010-2011 we invited all first comprehensive school students in Tromsø to the Fit Futures study and 1038 adolescents (93%) attended. We measured total body (TB), total hip (TH), and femoral neck (FN) areal bone mineral density (aBMD) as g/cm² by DXA (GE Lunar prodigy). Two years later, in 2012-2013, we invited all participants to a follow-up survey and 820 adolescents attended, providing 688 repeated measures of aBMD. Information on lifestyle were collected by questionnaires. Results: Girls between 17 and 19 years of age were approaching PBM at femoral sites, while boys were still accumulating bone mass between 17 and 19 years of age. There was a high degree of tracking of bone traits during two years in late adolescence and drift between quartiles was limited. Body weight and body mass index (BMI) were associated with bone accretion in late adolescence, but in a healthy young population, the influence and clinical implications were limited. However, low BMI was associated with low aBMD and particularly among boys with low BMI, an increase ...